The Influence of Accounting Knowledge on Career Interest as a Government Accountant among Untara Accounting Students - Dara Novita Fitrianingsih; Harmiyanto Pratama; Nazwa Nabila Putri; Shely Pebiyyanti; Dede Puspa Pujia (Penerbit Jurnal Indonesia, 2025)
This study aims to analyze the influence of accounting knowledge on career interest as a government accountant among accounting students. This quantitative study uses a survey approach using questionnaires distributed to 80 accounting students but only 50 students can be analyzed. Data were analyzed using linear regression with the help of SPSS version 29. To test the quality of the data, validity tests, reliability tests, and classical assumption tests were carried out. The results of the study indicate that accounting knowledge has a positive and significant effect on career interest as a government accountant (t count = 15.667; p < 0.01). The accounting knowledge variable is able to explain 51.5% of the variance in career interest, indicating a fairly strong influence. This finding emphasizes the importance of strengthening the public sector accounting curriculum in universities and the need for more intensive socialization regarding career prospects as a government accountant